Smart Grids Opportunities, Developments, and Trends - Ali, A B M Shawkat.; Ali, A B M Shawkat. (Green Energy and Technology,, 2013)
A Smart Grid delivers renewable energy as a main source of electricity from producers to consumers using two-way monitoring through Smart Meter technology that can remotely control consumer electricity use. This can help to storage excess energy; reduce costs, increase reliability and transparency, and make processes more efficiently. Smart Grids: Opportunities, Developments, and Trends discusses advances in Smart Grid in today’s dynamic and rapid growing global economical and technological environments. Current development in the field are systematically explored with an introduction, detailed discussion and an experimental demonstration. Each chapter also includes the future scope and ongoing research for each topic. Smart Grids: Opportunities, Developments, and Trends provides up to date knowledge, research results, and innovations in Smart Grids spanning design, implementation, analysis and evaluation of Smart Grid solutions to the challenging problems in all areas of power industry. Providing a solid foundation for graduate and postgraduate students, this thorough approach also makes Smart Grids: Opportunities, Developments, and Trends  a useful resource and hand book for researchers and practitioners in Smart Grid research. It can also act as a guide to Smart Grids for industry professionals and engineers from different fields working with Smart Grids.  .